Three-year experience of a dedicated prostate mpMRI pre-biopsy programme and effect on timed cancer diagnostic pathways. Issue 11 (November 2019) - Barrett, T.; Slough, R.; Sushentsev, N.; Shaida, N.; Koo, B.C.; Caglic, I.; Kozlov, V.; Warren, A.Y.; Thankappannair, V.; Pinnock, C.; Shah, N.; Saeb-Parsy, K.; et al.
Abstract : AIM: To evaluate the effect of pre-biopsy magnetic resonance imaging (MRI) on cancer diagnostic times, and to report MRI-directed pathology outcomes. MATERIALS AND METHODS: In total, 1483 patients were referred with prostate cancer suspicion during a 30-month period. Upfront MRI was performed in 745 patients: 332 MRIs in the 15 months prior to dedicated scanning slots (group 1), and 413 in the 15 months post-introduction (group 2). A further 88 patients had initial MRI following clinical assessment. Biopsy via the transrectal (TR) or transperineal (TP) approach was performed, with MRI/ultrasound fusion for MRI targets. Clinically significant cancer (csPCa) was defined as Gleason ≥3+4. Negative MRIs were defined as Likert 1–2. Per-case clinical decisions were taken to biopsy or not. RESULTS: 44.4% of patients avoided biopsy. 484/833 (58.1%) MRIs were negative; 37.4% of these patients had biopsy with a negative predictive value (NPV) of 92.8% for Gleason ≥3+4 and 98.3% for ≥4+3. Overall prostate cancer prevalence was 34.3% (24.6% csPCa). In 323 MRI-positive cases, any cancer was present in 78.9% (csPCa 60.4%). Of the 1483 patients, 1232 (83.1%) completed all diagnostic tests within 28 days. Upfront MRI patients met this standard in 621/833 (74.5%), improving from 66.9% to 81.1% with reserved slots (group 2) with a reduced diagnostic time from median 25.5 to 20.9 days. Biopsy scheduling delayed the pathway in 69.7%, with MRI responsible in 22.3%, reducing to 10.3% in group 2. TP biopsies met the 28-day standard in significantly less cases (29.7%), compared to TR (67.4%, p< 0.0001). CONCLUSION: Reserved MRI slots reduces time-to-diagnosis, and upfront MRI safely avoids biopsy in a significant proportion of men, whilst maintaining expected csPCa detection rates. Highlights: Overall biopsy avoidance rate in the upfront MRI cohort was 44% in a 3 year period. Use of reserved MRI slots reduced diagnostic time from median 25.5 to 20.9 days. NPV in men with negative MR undergoing biopsy for high clinical risk was high at 92%. Cancer detection matched literature reported rates for clinically significant cancer.